Characterization of imipenem resistance mechanisms in Pseudomonas aeruginosa isolates from Turkey - Mac Aogáin, M.; Kulah, C.; Rijnsburger, M.; Celebi, G.; Savelkoul, P.; O'Gara, Fergal; Mooij, M. (Blackwell Publishing, 2012)
The emergence of carbapenem resistance in Pseudomonas aeruginosa threatens the efficacy of this important anti-pseudomonal antibiotic class. Between 2003 and 2006, an increase in the number of carbapenem-resistant P. aeruginosa isolates at the Zonguldak Karaelmas University Hospital was observed (Zongul-dak, Turkey). To assess the imipenem resistance mechanisms emerging in these P. aeruginosa isolates, they were characterized by amplified fragment length polymorphism typing, which revealed diversity among imipenem-resistant isolates as well as two clonally related outbreak groups. The molecular mechanism of carbapenem resistance was characterized in a representative isolate from each clonal group. Mutational disruption of oprD was the most frequently encountered resistance mechanism (23/27 isolates).